2021
DOI: 10.1016/j.ijid.2021.10.009
|View full text |Cite
|
Sign up to set email alerts
|

The role of COVID‐19 survivor status and gender towards neutralizing antibody titers 1, 2, 3 months after Sinovac vaccine administration on clinical‐year medical students in Indonesia

Abstract: Background Sinovac was the first vaccine against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) used in Indonesia. However, data regarding the effects of certain variables such as clinical demographic on antibody levels in individuals vaccinated with Sinovac are scarce. We aimed to investigate the impact of gender and previous SARS-CoV-2 infection status on neutralizing antibody titers 1, 2, and 3 months after the administration of Sinovac vaccine. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…In our study, IgG Spike (RBD) levels within 2-4 months of vaccination were significantly higher in females compared to males. This finding is also reported in studies involving subjects across different nations, age groups and vaccine types (Heriyanto et al, 2021;Pellini et al, 2021;Terpos et al Excluding pre-vaccinated subjects (i.e., subjects who tested for antibodies prior to vaccination) and subjects with past COVID-19, Comirnaty vaccinees were found to have significantly higher IgG Spike (RBD) concentrations up to 4 months post-vaccination compared to ChAdOx1 and CoronaVac vaccinees (P<0.01) (Figures 1 and 2). Within one month of vaccination, Comirnaty vaccinees were found to have significantly higher IgM Spike levels (P=0.02) and remained positive up to 2 months of vaccination whilst ChAdOx1 and CoronaVac vaccinees largely tested negative within 1 month.…”
Section: Discussionsupporting
confidence: 72%
“…In our study, IgG Spike (RBD) levels within 2-4 months of vaccination were significantly higher in females compared to males. This finding is also reported in studies involving subjects across different nations, age groups and vaccine types (Heriyanto et al, 2021;Pellini et al, 2021;Terpos et al Excluding pre-vaccinated subjects (i.e., subjects who tested for antibodies prior to vaccination) and subjects with past COVID-19, Comirnaty vaccinees were found to have significantly higher IgG Spike (RBD) concentrations up to 4 months post-vaccination compared to ChAdOx1 and CoronaVac vaccinees (P<0.01) (Figures 1 and 2). Within one month of vaccination, Comirnaty vaccinees were found to have significantly higher IgM Spike levels (P=0.02) and remained positive up to 2 months of vaccination whilst ChAdOx1 and CoronaVac vaccinees largely tested negative within 1 month.…”
Section: Discussionsupporting
confidence: 72%
“…Interim evidence suggests that antibody levels in naturally-infected people persist for over 1 year [ 52 , 53 ]. Vaccine-induced immune responses in individuals with mild previous infection are generally higher [ 54 ], as previously infected individuals who were given one dose of a COVID-19 vaccine have higher responses than full-schedule vaccination of people who had not been previously infected [ 55 , 56 ]. Therefore, a one-dose schedule for previously infected individuals might be acceptable to achieve the dual purpose of protecting populations and saving supplies.…”
Section: Discussionmentioning
confidence: 99%
“…Bharat Biotech developed the inactivated BBV152 vaccine with 80% efficacy against COVID-19 (World Health Organization). Sinovac was the first vaccine used in Indonesia against COVID infection (Heriyanto et al, 2021). In Brazil trials, it was identified that Sinovac should be administered in 2 doses and shows the efficacy of 51% against symptomatic SARS-CoV-2 infection and it is 100% effective against severe COVID-19 infection after receiving a 2nd dose (Organization World Health, 2021).…”
Section: Introductionmentioning
confidence: 99%